(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Medico-legal autopsy profiling helps to understand the nature of causalities. It helps to assess the social and economic profile of the deceased. It is necessary for understanding nature of crime in particular area and with help of that it will helpful to identify the demographic needs and to take necessary preventive measures to stop the crime or unnatural deaths by means of spreading awareness and psychological counselling, if needed. This study is carried out retrospectively on death cases brought for medico-legal autopsies at mortuary of Civil Hospital and B. J. Medical College, Ahmedabad between January and December, 2019.